Factors Leading to a Poor Functional Outcome in Spinal Meningioma Surgery: Remarks on 173 Cases. Issue 4 (16th March 2017) - Raco, Antonino; Pesce, Alessandro; Toccaceli, Giada; Domenicucci, Maurizio; Miscusi, Massimo; Delfini, Roberto
Abstract: BACKGROUND: Spinal meningiomas are common spinal tumors, in most cases benign and with a good surgical prognosis. However, specific location, infiltration of spinal cord, vascular encasement, or spinal root involvement can bring a less favorable prognosis. OBJECTIVE: To correlate these data with clinical/functional outcome. METHODS: Two hundred twenty-four consecutive patients with spinal meningiomas treated from 1976 to 2013 in our institution were analyzed; among these, 51 were excluded for incomplete clinical data or follow-up. The remaining 173 cases were classified in regards to sex, age, symptoms, axial location, Simpson grade resection, and functional pre-/postoperative status. RESULTS: Most recurring onset symptoms were pain (32.9%) and motor deficit (31.8%); thoracic spine was the most severely affected (69.8%). Functional improvement on the follow-up was observed in 86.7% of cases; 6.4% of patients resulted stable and 6.9% worsened. A low functional grade before surgery was connected to a lesser improvement after. Anterolateral meningiomas were the most represented (42.2%); a gross total resection (Simpson grades I and II) was conducted in 98.8%, and a macroscopically complete removal without dural resection or coagulation (Simpson grade III) was performed in 1.2%. Of the meningiomas, 98.3% were classified as WHO grade I. Recurrence rate was 2.3%, and 7 cases presented complications (4 of 7 required surgical procedure). CONCLUSION: We can affirm that negative prognostic factors in our study were anterior or anterolateral axial location, prolonged presentation before diagnosis, WHO grade >I, Simpson grade resections II and III, sphincter involvement, and worse functional grade at onset.